2018
DOI: 10.1038/s41467-018-04271-z
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-elicited receptor-binding site antibodies neutralize two New World hemorrhagic fever arenaviruses

Abstract: While five arenaviruses cause human hemorrhagic fevers in the Western Hemisphere, only Junin virus (JUNV) has a vaccine. The GP1 subunit of their envelope glycoprotein binds transferrin receptor 1 (TfR1) using a surface that substantially varies in sequence among the viruses. As such, receptor-mimicking antibodies described to date are type-specific and lack the usual breadth associated with this mode of neutralization. Here we isolate, from the blood of a recipient of the live attenuated JUNV vaccine, two ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 63 publications
9
52
0
1
Order By: Relevance
“…Hence, such conformational switches may serve to form immunological decoys, in addition to priming the spike complexes for switching to secondary receptors. Receptor-binding sites are known vulnerabilities of viral glycoproteins (19,32,(36)(37)(38). In the case of GP1 LASV , a complete map of the ␣-DG binding site is still not available, but several residues that contribute to ␣-DG binding were previously identified (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, such conformational switches may serve to form immunological decoys, in addition to priming the spike complexes for switching to secondary receptors. Receptor-binding sites are known vulnerabilities of viral glycoproteins (19,32,(36)(37)(38). In the case of GP1 LASV , a complete map of the ␣-DG binding site is still not available, but several residues that contribute to ␣-DG binding were previously identified (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Both OW and NW arenaviruses display a glycoprotein complex, GPC, which is composed of a retained stable signal peptide, GP1 attachment glycoprotein, and membrane-anchored GP2 fusion glycoprotein. Structural studies have shown that the arenaviral GP1 presents a compact a/b fold, and the GP2 forms a class I type fusion architecture (Bowden et al 2009;Abraham et al 2010;Igonet et al 2011;Parsy et al 2013;Cohen-Dvashi et al 2015;Mahmutovic et al 2015;Hastie et al 2016Hastie et al , 2017Li et al 2016;Israeli et al 2017;Shimon, Shani, and Diskin 2017;Zeltina et al 2017;Clark et al 2018; Pryce et al 2018) (Fig. 1F).…”
Section: Discrete Structural and Functional States Of The Arenaviral Gp1mentioning
confidence: 99%
“…Due to the current paucity of GP2-bound NW GP1 structures, it is unknown whether the NW GP1 exhibits the same structural plasticity as OW GP1s. However, this has been hypothesized to be unlikely as GP2-free NW GP1 elicits a neutralizing antibody immune response following immunization in animal models, is recognized by vaccine-elicited neutralizing antibodies, and recognizes the host transferrin receptor 1 (Abraham et al 2010;Mahmutovic et al 2015;Zeltina et al 2017;Clark et al 2018;Borenstein-Katz et al 2019). A/Maryland H13 (4KPQ), A/Astrakhan H14 (3EYJ), A/Western Australia H15 (5TG8), A/Sweden H16 (4FIU), A/Guatemala HL17 (4I78), and A/Peru HL18 (4MC5).…”
Section: Discrete Structural and Functional States Of The Arenaviral Gp1mentioning
confidence: 99%
“…MAbs targeting sequence-conserved GP2 are considered very promising, while antibodies that cross-react with both NW and Old World arenaviruses neutralize neither (Amanat et al, 2018). NAbs for JUNV simply targeting GP1 have not been reported to have cross-neutralization capabilities against the five arenaviruses except for one elicited by Candid#1 that neutralizes both JUNV and MACV with varying efficiency in vitro (Clark et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several monoclonal antibodies (mAbs) against JUNV have been reported in recent years, including human-mouse chimaera mAbs modified by Zeitlin et al (2016), vaccine-elicited human mAbs discovered by Clark et al (2018), and a series of mouse mAbs identified by our group (Pan et al, 2018). These mAbs target the envelope glycoprotein complex (GPC) for neutralization, which consists of trimeric noncovalently bound subunits: receptor recognition subunit glycoprotein 1 (GP1), membrane-fusion subunit glycoprotein 2 (GP2), and stable signal peptide (SSP) (Radoshitzky et al, 2007;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%